Comparative Performance of PI And PID Controllers for Buck-Boost DC/DC Converter (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This paper describes design and implementation of a buck-boost DC-DC converter to control voltage regulation and achieve high efficiency using a proportional integral derivative (PID) and proportional integral (PI) method in MATLAB/Simulink. The converter is characterized by its ability to adjust the input voltage, either by increasing or decreasing it, to maintain a constant output voltage that meets the needs of various applications that require voltage stability under variable operating conditions, such as portable electronic systems and renewable energy systems. This paper describes an evaluation comparison of PID and PI for the performance of a buck-boost  converter and to achieve high power quality.